Red Seal Landscape Horticulturist Identify Plants and Plant Requirements - Nakano, Michelle (Open textbook library., 2020)
Red Seal Landscape Horticulturist Identify Plants and Plant Requirements is an adaptation of KPU HORT 1155 Introduction to Plant Materials Lecture Notes. It is an editable, open access learning resource with interactive web based experiences customized for horticulture students studying plant identification. This first edition supports student achievement of the Level 1 and 2 learning goals for Red Seal Landscape Horticulturist Line F2: Identify plant and plant requirements for a range of plants commonly used in horticulture Employ correct naming and plant identification terminology Identify morphological characteristics, growing requirements, use and availability Use a dichotomous key for plant identification Explain plant hardiness Identify weedy and invasive plants